2016
DOI: 10.1016/j.jtho.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

CT Features of Epidermal Growth Factor Receptor–Mutated Adenocarcinoma of the Lung: Comparison with Nonmutated Adenocarcinoma

Abstract: EGFR-mutated adenocarcinoma showed significantly higher frequencies of multiple bilateral lung metastases, convergence of surrounding structures, surrounding ground glass opacity, and notch at HRCT compared with the non-EGFR-mutated type. Conversely, EGFR-mutated adenocarcinoma showed cavity and pleural effusions less frequently than the nonmutated type did.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 36 publications
9
45
3
Order By: Relevance
“…A few studies have suggested that patients carrying an EGFR activating mutation may present a higher frequency of pulmonary, multiple, bilateral metastases [16, 23]. Likely to the small sample size, we failed to demonstrate a statistically significant difference between EGFR mutated and wild type NSCLCs, albeit a positive trend favoring an increased tendency to lung metastatization was observed ( p = 0.14),…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…A few studies have suggested that patients carrying an EGFR activating mutation may present a higher frequency of pulmonary, multiple, bilateral metastases [16, 23]. Likely to the small sample size, we failed to demonstrate a statistically significant difference between EGFR mutated and wild type NSCLCs, albeit a positive trend favoring an increased tendency to lung metastatization was observed ( p = 0.14),…”
Section: Discussioncontrasting
confidence: 75%
“…Indeed, some Authors have reported a higher tendency to develop BMs among ALK-rearranged NSCLCs [19], which in some instances might be associated with specific radiological patterns, such as miliary distribution [20] or cystic lesions [21, 22]. Moreover, others have reported specific radiographic features [2325] and bronchoscopic findings in EGFR mutated NSCLCs [26]. …”
Section: Introductionmentioning
confidence: 99%
“…Although no significant association was found between GGO and EGFR mutations (P=0.07), the EGFR mutation occurred more frequently in male patients with GGO than in those without GGO. Furthermore, two studies (41,42) involving 263 and 285 lung adenocarcinoma, reported that the EGFRmutated group had significantly higher frequencies and no higher frequencies of GGO, respectively. Lee et al (6) found that GGO volume percentage in tumors with L858R mutation was significantly higher than that in EGFR wildtype tumors (P=0.0001) and 19 deletion mutated tumors (P=0.0006).…”
Section: Molecular Pathology and Ct Featuresmentioning
confidence: 99%
“…A recent study looking at CT findings and EGFR mutation status, reported that EGFR-mutated adenocarcinoma had significantly higher frequencies of multiple bilateral lung tumors, convergence of surrounding structures, surrounding ground glass opacity, and notch sign at HRCT compared with the non-EGFR-mutated type (1415). Cavitation and pleural effusions less frequent when compared to the non-mutated subtype (1415). …”
Section: Comparison Of Egfr and Alk In Nsclcmentioning
confidence: 99%